Involuntary movement in an emotionally labile girl : Think of Wilson’s Disease (Bangladesh Critical Care Journal, 2018)
Wilson’s Disease (WD) is a rare, autosomal recessive, inborn error of copper metabolism, which is caused by a mutation in the copper-transporting gene, ATP7B. The presentation is usually neurologic or hepatic or both, which is seen in 40% of the patients. The diagnosis depends primarily on the clinical features, the biochemical parameters and the presence of the Kayser – Fleischer ring. Here, we are reporting a 13 years old girl who was affected by Wilson’s disease, with both neurological manifestations & hepatic involvement.Bangladesh Crit Care J March 2018; 6(1): 57-59